Pendampingan Digital Marketing bagi UMKM di Desa Wisata Bumiaji: Digital Marketing Assistance for MSMEs in Bumiaji Tourism Village - Rahayu, Sri Mangesti; Anjarwi, Astri Warih; Anggoro, Damas Dwi; Alfandia, Nurlita Sukma (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
MSME owners must employ digital media to promote their products effectively. Micro, Small, and Medium Enterprises (MSMEs) that possess online connectivity, utilize social media platforms and enhance their e-commerce capabilities would attain more incredible business growth and profitability advantages than MSMEs that still need to acquire these skills. The purpose of conducting community service activities in 2023 is to aid MSME owners in the surrounding area with digital-based marketing so that they may stimulate the economy of Bumiaji Tourism Village to become an autonomous and progressive village. The Batu Orange Cake shop based in the Bumiaji Tourism Village is the focus of the internet marketing campaign. The implementation approach elucidates the sequential stages of executing the proposed solution to address partner issues, specifically the planning and execution phases. Community outreach initiatives are scheduled to take place from August to October 2023. This mentorship activity focuses on supporting the proprietor of Oren's Cake company in the Bumiaji Tourism Village, specifically in social media marketing. The service team collaborated in producing a video that will be utilized as Batu Orange Cake's content on Instagram. In addition, support is offered in utilizing Instagram as a platform for digital marketing. The expectation is that upon completing this activity, Instagram account owners and managers will retain the ability to continue using Instagram.